Implementation Design Thinking in Google Sites with TaRL-Approach to Improve Mathematical Problem-Solving Skills - Harpeningtyas, Rinayanti Budi; Nizaruddin, Nizaruddin; Dwijayanti, Ida (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
The 21st century requires individuals toahaveatheaabilityato think_comprehensively, especially in criticalaandacreative_thinking. The result of the PISA study show that the literacy skills of Indonesian student are still relatively low, including in terms of numeracy or mathematical problem solving. Preliminary data shows that most students have a "normal" feeling about math lessons (45%) and feel less confident when-learning maths (47.2%). Teachers also face difficulties in providing learning materials that_are in-accordanceawith the level of students' abilities due to heterogeneity in the classroom. Thisastudyaaimsatoadetermine theaeffectivenessaofagoogleasites-basedalearning media with the integration of design thinking and ADDIE as a development approach, as well as using the Teaching at the Right Level-(TaRL) method in media preparation. The stages  of empathize, -define, ideate, aprototype, aandatestainadesignathinking are combined with the-ADDIE (Analysis,aDesign,aDevelopment,aImplementation, Evaluation) cycleatoaproduceamediaathatasuits the needs of students. The-subject ofathis study-is a-grade XI-student of State High School 4 Semarang. The results of data analysis showed anaincreaseainathe-mathematical problem-solving-abilityaofastudents with an-N-Gainascoreaofa0.7 (high-category) and t-test results of 1.711 which is greater than the t-table of 1.67. In addition, thearesultsaofatheaanalysisaof-the classical-learning-completenessatest show that theaproportion of completeness of materialistic problem ability is achieved. Theoretically, this research contributes to the study of technology-based learning with the application of TaRL, and is able to support constructivistic theory and effectively improve students' mathematical problem-solving skills.